Emissions From an Engine Fueled With Biodiesel-kerosene Blends - Aydin, H.; Bayindir, H.; Ilkilic, C. (Taylor & Francis Inc, 2011)
Biofuels are renewable energy sources for internal combustion engines and they have low emissions. They are increasingly used as an alternative to petroleum fuels. In this work, three different fuel types, such as commercial diesel fuel (D2), 20% biodiesel and 80% diesel fuel called here as B20, and 80% biodiesel and 20% kerosene, called here as BK20, were used in a single cylinder, four stroke, direct injection compression ignition engine. Kerosene was used as an additive to approach the properties of biodiesel to D2. The effects of the blends on CO, NOx, and smoke emissions as well as on some of the performance parameter of the engine were investigated. The prepared fuel, BK20 blend, has almost the same fuel properties as conventional diesel fuel. The experimental results showed that the exhaust emissions for BK20 were fairly reduced as compared to diesel fuel as well as B20. Besides, the performance of CI engine was improved with the use of the BK20, especially in comparison to B20. Results suggest that the BK20 can be substituted to the petroleum-based diesel fuel in diesel engines.
Keywords: alternative fuel; biodiesel; bio-kerosene; diesel engine; emissions